Product Placement dalam Drama Korea Populer “The World Of Married” - Anisa Nur Andina; Adipura Arya Kangsadewa; Zhafira Atika Anggrani (CV. Ridwan Publisher, 2021)
Abstract Product placement is an advertising technique that intentionally places a product or brand on an entertainment event, either through films or television shows. In this study, there are several brands that are included in the popular Korean drama The World of The Married which have received attention from consumers so that their sales have increased dramatically. The research method used is descriptive qualitative with a phenomenological approach. While the data collection technique used interviews and observations of fans of the Korean drama The World of The Married. The results of research on product placement that were carried out showed that brands that did product placement in popular Korean dramas increased their profits because consumers were interested in these brands. Abstrak Product placement merupakan salah satu teknik beriklan yang dengan sengaja menempatkan produk atau merek pada acara hiburan baik melalui film maupun acara televisi. Pada penelitian ini terdapat beberapa merek yang masuk ke dalam drama Korea populer The World of The Married yang mendapat perhatian dari konsumen sehingga penjualannya meningkat drastis. Metode penelitian yang digunakan adalah kualitatif deskriptif dengan pendekatan fenomenologi. Sementara teknik pengumpulan data menggunakan wawancara dan observasi penggemar drama Korea The World of The Married. Hasil penelitian tentang product placement yang dilakukan didapatkan bahwa merek yang melakukan penempatan produk pada drama Korea populer keuntungannya meningkat karena konsumen tertarik pada merek-merek tersebut.